New records of mosquitoes from the southern Brazilian States of Santa Catarina and Rio Grande do Sul, with 18 species new for the States (Diptera: Culicidae) - Marcondes, Carlos Brisola; Fernandes, Aristides; Paterno, Uéslei; Müller, Gerson Azulim; de Pinho, Luiz Carlos; Struffaldi, Denis Volkman (Zootaxa, 2003)
Records of mosquitoes not related to malaria or filariasis in the two most southern states of Brazil (Santa Catarina and Rio Grande do Sul) are scanty. We report the finding of 18 species new for these states: Aedeomyia squamipennis, Ochlerotatus albifasciatus, Oc. fulvus, Oc. rhyacophilus, Oc. terrens, Psorophora lutzii, Runchomyia cerqueirai, Ru. theobaldi, Sa. melanonymphe, Trichoprosopon pallidiventer, Wyeomyia argenteorostris, Wy. bourrouli, Wy. cesari/moerbista, Wy. edwardsi, Wy. lutzi, Wy. quasilongirostris, Wy. tarsata and Wy. tripartita. Other species are referred for some peculiarity. Their possible medical and veterinary importance is commented.